Brachyuran crab diversity across spatial and temporal scales in a mangrove ecosystem from the western Atlantic - Freitas, Felipe; Pescinelli, Régis A. [UNESP]; Costa, Rogerio C. [UNESP]; Hilesheim, Juliano C.; L. Dieh, Fernando; Branco, Joaquim O. (Elsevier, 2021)
Brachyuran crabs are considered ecosystem engineers which greatly impact energy flow and are an important link between the base and higher trophic levels in mangrove forests. Thus, their richness and abundance configure a potential ecological indicator of habitat disturbance. Herein, we spatially and seasonally investigated the crab diversity throughout an eight-year time span in a subtropical mangrove. Sampling was performed seasonally from 2011 to 2019 in five sites located in the Babitonga bay mangrove ecosystem. Our results indicate significant differences in the richness, diversity, and abundance among years and among the sites, as well as significant associations and interactions between the abundance and distribution of the crabs’ assemblage across temporal and spatial scales. Sites 3 and 2 showed the highest richness, followed by sites 5, 4 and 1, respectively. Temporal analysis showed small fluctuations among the years, with 2011–2012 showing higher richness than the other periods. Ocypodidae was the most dominant family. The fiddler crab Leptuca thayeri was the most abundant in all sites, except site 3, which presented L. leptodactyla as the most abundant, indicating ecosystem disturbances for sites 2 and 3 as they were the closest to anthropized areas. All results indicate the importance of the brachyuran crab assemblage for characterizing and evaluating the mangrove ecosystem of Babitonga bay, making them fundamental for monitoring and developing plans aimed at reducing the impacts of adjacent anthropized areas.
Keywords: Babitonga bay; Biodiversity; Crabs’ assemblage; Crustacea; Subtropical mangroves